AePS – A Step Forward: Indian Perspective - Abhimanyu Sasi Pavoor; N. Ajithkumar (Communications of International Proceedings, 2020)
Aadhaar Enabled Payment System (AePS) is a payment method that is widely used in India. This paper assesses and evaluates AePS payment system. It was introduced and established by National Payments Corporation of India(NPCI). This payment method helps in performing electronic transactions using Micro ATMs. It crosschecks the Aadhaar numbers and biometrics of the respective customer. The focal point of this paper is to acquaint public, the impact of AePS on digital payments in India. This is done by examining various literatures in Indian scenario. AePS has developed a powerful digital payment network. Real time verification of biometrics and Aadhaar number is done in this payment network. The main aim of this system is to promote financial inclusion. Now AePS is currently in a developmental stage. RBI and NPCI have made significant steps in discovering new areas to improve the payment system networks. AePS has helped in preventing illicit payments and also helped in blocking unauthorized direct benefit transfers.
Keywords: Digital payments; National Payments Corporation of India; Aadhaar Enabled Payment System; Biometric; Micro ATM